2012
DOI: 10.1128/aac.05214-11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Pharmacokinetic Interaction between Eltrombopag and Lopinavir-Ritonavir in Healthy Adult Subjects

Abstract: Eltrombopag is an orally bioavailable thrombopoietin receptor agonist that is approved for the treatment of chronic idiopathic thrombocytopenic purpura. It is being developed for other medical disorders that are associated with thrombocytopenia. Patients with human immunodeficiency virus (HIV) may suffer from thrombocytopenia as a result of their HIV disease or coinfection with hepatitis C virus (HCV). HIV medications, particularly ritonavir (RTV)-boosted HIV protease inhibitors, are involved in many drug inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The safety monitoring data of other studies are mainly concentrated in patients with AIDS and healthy people. 18,19 For example, as seen in the Gonzalez-Garcia et al study, the most frequently reported AE in healthy adult subjects was diarrhea (26/40; 65%). 18 A randomized trial to evaluate the efficacy and safety of lopinavir/ritonavir in the treatment of HIV-1 infection reported that the incidence of diarrhea in moderate/severe AEs was 16%.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The safety monitoring data of other studies are mainly concentrated in patients with AIDS and healthy people. 18,19 For example, as seen in the Gonzalez-Garcia et al study, the most frequently reported AE in healthy adult subjects was diarrhea (26/40; 65%). 18 A randomized trial to evaluate the efficacy and safety of lopinavir/ritonavir in the treatment of HIV-1 infection reported that the incidence of diarrhea in moderate/severe AEs was 16%.…”
Section: Discussionmentioning
confidence: 88%
“…To evaluate the incidence, type, and risk factors associated with adverse drug reactions (ADRs) among patients with coronavirus disease 2019 (COVID- 19) by Hospital Pharmacovigilance System (CHPS). A retrospective analysis was performed on 217 patients with COVID-19 admitted to the First Hospital of Changsha in China, from January 17, 2020, to February 29, 2020.…”
Section: Incidence Of Adverse Drug Reactions In Covid-19 Patients In mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the intra-subject coefficient of variation of 15% for PK parameters for LPV, 19 a 5% consumer risk with 80% power, and assuming no difference between treatments, 16 subjects were necessary to demonstrate equivalence within the conventional acceptance range of 0.80–1.25 applied for bioequivalence studies. 20 …”
Section: Methodsmentioning
confidence: 99%
“…Clinical drug–drug interactions (DDIs) have been observed between eltrombopag and rosuvastatin (as a perpetrator 13 ) and lopinavir–ritonavir (as a victim 14 ). The main cause of the interaction of eltrombopag with rosuvastatin in vitro was the result of BCRP inhibition, with minimal inhibition of OATP1B1 5,15 .…”
mentioning
confidence: 99%